T.C.Merkez Bankasının bağımsızlığı ve Türkiye’de izlenen para politikaları - Bıyık, Hasibe (My University, 1999)
Turkey's Foreign Debt Problem - Its Extents and Causes Govemments finance their domestic loans from a number of different sources, the most important ones being loans raised from private persons and companies, borrowing from social security institutions, from commercial banks and from the Central Bank. Selection of the source basically depends on the economic trends; If the economy is under the pressure of inflationistic price increases, borrowing must be must be done from private individuals and Companies in order to reduce and control the total volume of spending. If on the contrary, the economy is stagnant and un-employment very high, borrowing should rather be done from the Central and Commercial Banks. Depending on the source of borrowing, domestic loans have profound effects on the economy; variables such as the interest rates, the inflation index and foreign exchange rates have an important influence. Consequently, all aspects of the economy such as investments, production, employment, distribution of income and economic stability of a country are greatly affected directly or indirectly by the manner of domestic borrowing. The basis reasons for the increase in Turkey's domestic debts, is the need to finance public sector deficits, and the fact that new borrowings are required to re-pay previous loans. On the other hand, public sectors deficits consist of consolidated budget deficits, of Social Security institutions and KIT (Public Economic Enterprises) deficits, as well as the deficits of un-budgeted funds. To these must be added the borrowing of funds needed to maintain a financial discipline in the public sector in the exercise of an election economy. A solution must be reached urgently to settle the question of domestic borrowing which is such an important factor in Turkey's economy. However, a short term solutions to the problem appears rather difficult, and for that reason, answers must be sought in the frame of medium and long term structural measures. The first thing to do is to maintain a policy of balanced budget for a rather long period. In addition, the public sector must be re-structured, the KIT privatized, and the possibilities of fundamental measures such as the Reform of the Social Security Institutions, and the improvement of policies on Agricultural Price Subsidies have to be considered very seriously. T.C. Central Banks Autonomy and Turkey's Monetary Policies Realization of Central Banks' primary role as regulatory instruments in the application of monetary policies, and admission of the importance in their being independent from all sorts of political authority, has lately activated debates on the subject. We will at first make a general study of the Turkey's Central Bank's autonomy and then proceed by considering the effect of this independence on monetary policies. Although at first, Central Banks started to perform their functions and were held responsible for the application of monetary policies as a dependents of the political authority, importance of their autonomy kept increasing. The degree of juridical economic, political and effective autonomy of Central Banks was investigated and found to be higher in developed countries than in developing countries. Its worthwhile to note that Central Banks with a higher degree of independence were mostly those in developed countries enjoying a generally lower inflation rate. The date studied shows that Central Banks in developed countries such as Germany, the United States, Switzerland and Canada, have a considerably higher degree of independence. One observes that the degree of autonomy of the T.C. Central Bank is far from the required level. Results of the investigations show that while from the juridical point of view the T.C. Central Bank, in the 9th position after such countries as Canada, The Netherlands, Great Britain, etc., differences are observed in the applications. One of the most important factor influencing the T.C. Central Bank's independence, it its function of having to finance public sector deficits. In harmony with developments in Turkey's and World economy, some new arrangements have been brought to the T.C. Central Bank's structure, to its management and to the instruments it uses in its control of monetary policies. Nevertheless, the continuation for long period of a high rate of inflation, the ever-increasing budgetary deficits, the great difficulties in the financing such deficits, as well as the macroeconomic uncertainties related to monetary policies have prevented the Central Bank of attaining the desired level of autonomy. The importance of such an autonomy will be far better understood if one considers the extent to which T.C. Central Bank's current financial instruments of re-discount and legal provision policies, its open market operations etc. Are effective in Turkey's present monetary policy.
Keywords: MERKEZ BANKASI